Dynamics of retracting surfactant-laden ligaments at intermediate Ohnesorge number - Constante-Amores,CR; Kahouadji,L; Batchvarov,A; Shin,S; Chergui,J; Juric,D; Matar,OK (Physical Review Fluids, 2020)
The dynamics of ligaments retracting under the action of surface tension occurs in a multitude of natural and industrial applications; these include inkjet printing and atomization. We perform direct, fully three-dimensional, two-phase numerical simulations of the retracting process over a range of system parameters that account for surfactant solubility, sorption kinetics, and Marangoni stresses. Our results indicate that the presence of surfactant inhibits the “end-pinching” mechanism and promotes neck reopening through Marangoni-flow; this is induced by the formation of surfactant concentration gradients that drive flow-reversal toward the neck. The vortical structures associated with this flow are also analyzed in detail. We also show that these Marangoni stresses lead to interfacial rigidification, observed through a reduction of the retraction velocity and ligament kinetic energy.